Metode Pakistan dalam Membaca dan Menulis Al-Qur'an - Dede Ar Rosyid; Syarifan Nurjan; Bagus, Agan Priam; Syamsul Arifin; Amin, Mohd Yasin bin Mohd (International Journal of Learning and Education, 2025)
This study evaluates the effectiveness of the Pakistani Method in enhancing Quranic reading and writing skills (BTQ) among students at Madrasah Diniyah Daarul Ilmi, in response to the widely reported low levels of Quranic literacy. The research employs a quantitative experimental design with a population of 50 students, all of whom were included as the sample. Data were collected through questionnaires, observation, and documentation, and analyzed using validity and reliability tests, normality tests, homogeneity tests, and hypothesis testing (F-test, t-test, and R²). The analysis results indicate that the data are valid and reliable, with a Cronbach’s Alpha of 0.879. Prerequisite tests confirm that the data are normally distributed and homogeneous. Hypothesis testing yields an F-value of 228.921 (p=0.00), a t-value of 15.130 (p=0.00), and a coefficient of determination (R²) of 82.7%, statistically confirming that the Pakistani Method has a significant and effective influence on improving BTQ skills. The discussion reveals that the strength of this method lies in its structured, integrative, and phonocentric approach, which simultaneously teaches reading fluency, mastery of tajwid, and Arabic orthographic competence. The conclusion affirms that the Pakistani Method is an evidence-based pedagogical alternative capable of addressing the shortcomings of conventional methods. The implications suggest that this method can be adopted in curriculum development and teacher training for Islamic religious education. Future research is recommended to examine the long-term sustainability of its effects and the method's adaptation across diverse educational contexts and institutions.